Ultrasound irradiation synthesis and crystal structure of Co(II) thiocyanate supramolecular complex: Photocatalytic and sonocatalytic degradation of methyl violet 2B dye. (6th January 2021) - Etaiw, Safaa El‐din H.; Shalaby, Elsayed M.; Abd El‐Aziz, Dina M.; Elzeny, Islam
Abstract : ∞ 3 [{Co(hmt)2 (NCS)2 (H2 O)2 }{Co(NCS)2 (H2 O)4 }(2H2 O)] supramolecular complex (SC ) had been synthesized through self‐assembly reaction using the sonochemical method at ambient conditions. The structure was fully characterized by single‐crystal X‐ray diffraction and spectroscopic methods. The structure consists of two separate distinct complexes containing two crystallography and chemically different Co II atoms, four thiocyanate ligands, two hmt ligands, six coordinated water molecules, and one uncoordinated water molecule. The two Co II (SCN)2 fragments adopt 1D chains which extend three dimensionally via strong H bonds. Radiation catalysis is a promising wastewater treatment method, which is used to remove dyes under UV and ultrasonic radiation in the presence of a heterogeneous catalyst. SC exhibits efficient heterogeneous catalysis for degradation of methyl violet 2B (MV2B) dye which was used as a model pollutant in presence of H2 O2 under ambient conditions. UV irradiation and ultrasonic irradiation reveal significant enhancement in degradation efficiency and time. The morphological features of SC are examined by transition electron microscopy (TEM) and scanning electron microscopy (SEM) before and after degradation. Abstract : ∞ 3 [{Co(hmt)2 (NCS)2 (H2 O)2 }{Co(NCS)2 (H2 O)4 }(2H2 O)] supramolecular complex (SC ) has been synthesized through self‐assembly reaction and sonochemical methods at ambient conditions. The structure was fully characterized by single‐crystal X‐ray diffraction and spectroscopic methods. SC is used as heterogeneous catalyst for removal degradation of methyl violet 2B (MV2B) dye under ambient conditions, UV irradiation, and ultrasonic irradiation.